Human resource development : vol. II : prime minister's rozgar yojna - Mehta, Basant; Kothari, Kiran (New Delhi : Discovery Pub. House, 1999)
Study relates to Kota and Udaipur districts of Rajasthan.
v. 1. Training of rural youth for self-employment -- v. 2. Prime Minister's Rozgar Yojna.
Includes bibliographical references (v. 1, p. [170]-186); v. 2, p. [138]-154) and indexes.
Keywords: Manpower policy, Rural -- India; Rural youth -- Employment -- India; Rural development -- India